Effects of ludic activities on the development of writing skills in 5 th year students at unidad educative Liceo Cristiano de Guayaquil campus 1 - Caicedo Vargas, Lady Thalia (2016)
This research project looks for determining the effects of ludic activities on the development of writing skills in 5 th- year students at Unidad Educative Liceo Cristiano de Guayaquil campus 1. Because of the writing skill problems that were observed during the classes, it was proposed to conduct a careful study to find and analyze the reasons of those problems. The information necessary was taken based on other researchers and investigations about the development of writing skills and the use of ludic or playful activities.............